Plan de mejoramiento empresarial Abanico Floristería (2015)
In the environment of small business in the region, is included which must Fan Florist From handled methodically and strategically, displaying Thus the negocion As a large Company. CURRENTLY she florist Despite his great experience in the market, selling Variety of floral compositions to face situations that restrict business efficiency, So that with previous analyzes External and Internal illustrated in matrices EFAS mail IFAS Opportunities, Threats, Strengths and Weaknesses are evident mainly generated A great support for the improvement and creation in the areas, administrative, commercial, financial and productive, that drive solutions that generate productivity and profitability. This is to be achieved para Impact v Florist UN and within the environment, Shown in the Improvement Plan Company, through whatever Fan Florist, Take a corporal the study, diagnosis and formulation of strategies that best suit the Development Goals. In the preparation of this Improvement Plan's approach it is presented to the Company Problem in Chapter 1, from which is derived Order UN para esta Solution of equally Objectives, specific and general therefore required Reaching the presents Information type of study and research method in Chapter 2 indicated the Review Historical whatever it gives us the details of the history of the Organization and its position Current, then chapter 3 and 4 where the external and internal analysis by plasma planted They conclude matrix SWOT matrix of one paragraph Creation Strategies counter Thus identified shortcomings continue with Chapter 5 Forging Development Support Analysis processes information Competition and Best of copies of Business Floral compositions, so that in the final chapters 6,7 and 8 point out the A general strategies emphasized Fan Florist in each required area, its estimate of Costs Runtime and Monitoring plan for measuring the success of This Project.